On the Treatment of Finance-Specific Factors Within the OLI Paradigm - Lars Oxelheim; Trond Randøy; Arthur Stonehill (The Research Institute of Industrial Economics (IUI), 2001)
This article argues that the body of foreign direct investment (FDI) literature in general and the ownership, location, and internalization (OLI) paradigm in particular would be enriched if finance-specific factors are explicitly incorporated as drivers of FDI. We suggest that financial strategies involving factors such as debt/equity swaps or equity-listings in foreign equity markets affect the firms relative cost and availability of capital, and motivate a firms engagement in FDI. Large, research-intensive firms, predominantly resident in the US, UK, Japan or other liquid markets, have in the literature been identified as typical prototypes of MNEs undertaking FDI. These firms are assumed to have no restrictions as regards their ability to achieve a competitive cost and availability of capital, a focus that has made financial capabilities and resources less of an issue in FDI research. Our article mitigates this by emphasizing the relevance of finance-specific proactive strategies for FDI to occur. We generate eight testable hypotheses based on the recognition of finance-specific factors as active drivers of value creating FDI.
Keywords: F21; F23; G34; M21; 330; FDI; Cost of capital; Financial strategies; OLI; Auslandsinvestition; Unternehmensfinanzierung; Multinationales Unternehmen; Theorie